Short Communication: The Belly–Tendon Derivation Yields Superior Ocular Vestibular Evoked Myogenic Potential Amplitudes in a Normal Pediatric Sample - Bilodeau, Megan; Jacobson, Gary P.; Roberts, Richard A.; Hatton, Kelsey (American journal of audiology, 2020)
Purpose The purpose of the investigation was to determine whether the "belly-tendon" electrode derivation produced ocular vestibular evoked myogenic potentials (oVEMPs) in children that were superior to those recorded with the infraorbital-chin electrode derivation. Method This was a prospective observational study using a sample of convenience at a tertiary care medical center. Subjects were 13 children between the ages of 5 and 12 years. We compared the latency of the N1 wave and the N1-P1 peak-to-peak amplitude for the belly-tendon electrode derivation to the infraorbital-chin electrode derivation. Results The belly-tendon electrode derivation was associated with superior N1-P1 amplitudes compared to the infraorbital-chin electrode derivation. However, the large amplitude was also associated with greater variability compared to the infraorbital-chin derivation. There were no significant electrode derivation-based differences in N1 latency. Additionally, there was no predictable relationship between age and oVEMP amplitude. Conclusion As shown previously in adults, the belly-tendon electrode derivation produces significantly larger oVEMP amplitudes compared to the infraorbital-chin electrode derivation.